DEVELOPMENT OF SOLAR SYSTEM SIMULATOR MEDIA FOR ELEMENTARY SCHOOLS. - Sari, Desi Wulan; Subayani, Nataria Wahyuning; Marzuki, Ismail (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
This This study aims to develop a solar system simulator learning media for solar system material in grade VI elementary school, and determine the quality of the media through the results of validation, validity, and practicality. The type of research used in this research is development research using modified and simplified 4-D development research methods, namely defining, designing, developing and without disseminating. Development in the form of a solar system simulator media which is made to describe a small version of the solar system equipped with a user manual. Sources of data in this development research are students of class VI UPT SD Negeri 110 Gresik, totaling 30 students. The data collection techniques used in this study were the validation of learning media, student response questionnaires, and learning outcomes tests. The data analysis technique used in this research is the analysis of the validity of the learning media, the analysis of the effectiveness of the learning media, and the analysis of the practicality of the learning media. The results of descriptive analysis of the validation results and test data obtained that the development of learning media for solar system simulators for class VI solar system material at UPT SD Negeri 110 Gresik met the good criteria, namely as follows: a) The results of the validation of learning media conducted by the validator obtained a percentage 87.5% which is categorized as valid and can be used during the learning process, b) Categorized as effective from the results of learning mastery analysis, the results of the percentage of classical learning mastery are 86.7%, it can be said that students' learning mastery is achieved, c) Categorized practically from the results of the analysis of student responses, the percentage of student responses is 94.7%, it can be said that the solar system simulator media is in the good category. The implication of this research is that it can result in the development of quality media to help deliver material on the solar system so that it has a very good contribution to the world of education. The solar system simulator media can explain directly the process of the solar system with visualization from the front. So that educators have no difficulty in giving explanations to students about the material of the solar system because it has been helped by the media simulator of the solar system. In addition, this media can make it easier for studentsto understand the concept of the solar system and reduce students' misconceptions in learning the solar system. This development research produces concrete learning media that are in accordance with the solar system learning material in grade VI elementary school. However, this research is limited to its visualization, the visualization of this media can only be seen from the front.